2004
DOI: 10.1182/blood-2003-12-4241
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-α blockade for the treatment of acute GVHD

Abstract: Despite posttransplantation immunosuppressive therapy, acute graft-versus-host disease (GVHD) remains a major cause of sickness and death. Tumor necrosis factor-␣ (TNF-␣) is implicated in the pathophysiology of GVHD at several steps in the process. Infliximab is a genetically constructed immunoglobulin G1 (IgG1) murine-human chimeric monoclonal antibody that binds the soluble subunit and the membrane-bound precursor of TNF-␣, blocking its interaction with receptors and causing lysis of cells that produce TNF-␣… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
176
2
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 253 publications
(191 citation statements)
references
References 48 publications
10
176
2
3
Order By: Relevance
“…As many of these chemokines are synthesized by macrophages, we speculate that their increased expression in mice infected with the Δ gliP mutants was due to reduced death of macrophages in the fungal lesions. In mice infected with the Δ gliP mutant, there was also elevated expression of IL-6 and TNF-α, suggesting that gliotoxin also inhibits the production of these cytokines, both of which are required for the host defense against invasive aspergillosis [3638]. …”
Section: Discussionmentioning
confidence: 99%
“…As many of these chemokines are synthesized by macrophages, we speculate that their increased expression in mice infected with the Δ gliP mutants was due to reduced death of macrophages in the fungal lesions. In mice infected with the Δ gliP mutant, there was also elevated expression of IL-6 and TNF-α, suggesting that gliotoxin also inhibits the production of these cytokines, both of which are required for the host defense against invasive aspergillosis [3638]. …”
Section: Discussionmentioning
confidence: 99%
“…24 Other phase II studies that addressed blocking of proinflammatory cytokines (for example, TNF-a and IL-2) with MoAbs resulted in overall CR rates of 47, 53 and 62% for daclizumab, basiliximab and infliximab, respectively. [25][26][27] In the study by Przepiorka et al using daclizumab, a specific CR rate of 37% was reported for GI GVHD. A CR rate of 67% was reported for infliximab by Couriel et al However, only 3 of 12 subjects had grade X3 GI GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study, infliximab has been shown to be associated with significant response although the proportion of patients with grade III-IV aGVHD was low and treatment was complicated by infections particularly aspergillus which could be explained by elimination of monocytes-macrophages by infliximab [97,98]. Etanercept also increased infections in clinical trials but not as much as infliximab [81,86].…”
Section: Anti-tnfα Agentsmentioning
confidence: 99%